HUBUNGAN KESEPIAN DENGAN KESEJAHTERAAN SPIRITUAL PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA UNIT BUDI LUHUR YOGYAKARTA - , DIAN ANDRIANI; , dr. I Dewa Putu Pramantara Sp. PD, K-Ger. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
psychological problem most common in elderly. Elderly who live in an institution suffering from loneliness and feel dissatisfied because apart from the family and the wider community. Religious and spiritual coping resources that are typically used by elderly when experiencing sadness, loneliness and loss. Objective: This study aims to know association between loneliness and spiritual well being among elderly Methods: Types of non-experimental research using cross-sectional design. This study uses a quantitative approach to correlational analytic methods. Subjects were elderly men and women who reside in Panti Sosial Tresna Werdha Unit Budi Luhur Yogyakarta. Respondents are 40 people with the inclusion criteria elderly men or women aged 60 years or older, able to communicate well and be willing to respondents, whereas the exclusion criteria elderly who experience mental disorders according to data from Panti Sosial Tresna Werdha Unit Budi Luhur Yogyakarta, and elderly people living in isolation and in a state or bed rest. Research tool used was a questionnaire UCLA Loneliness Scale Version 3 and questionnaires Spiritual Well Being Scale (SWBS). Result: Most of elderly in Panti Sosial Tresna Werdha Unit Budi Luhur Yogyakarta experiencing loneliness, as many as 23 of the 40 elderly people or 47.5%. Most of elderly in Panti Sosial Tresna Werdha Unit Budi Luhur Yogyakarta has high spiritual well being of as many as 28 of 40 people or 70%. There is a significant association between loneliness and spiritual well being of elderly in Panti Sosial Tresna Werdha Unit Budi Luhur Yogyakarta with a significance value of p = 0.003 (p <0.05) Conclusions: There is a negative relationship between loneliness and spiritual well being of the elderly in Panti Sosial Tresna Werdha Unit Budi Luhur Yogyakarta.